Counteracting crime: axiological aspect - Podkovenko, Tetiana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article analyzes the current state and dynamics of crime in Ukraine through the prism of the axiological standards of a democratic society. In the conditions of the rule of law, the problem of protecting its citizens from criminal encroachments, as well as counteracting attempts to criminalize society, neutralize negative social trends are of paramount importance. In this context, the issues of combating crime, crime prevention and other offenses, and preventive work with the population are particularly acute. Based on current perceptions of the nature of crime, it is determined that counteracting crime and its manifestations is a system of social and legal efforts aimed at preventing and responding to criminal offenses. The problems of the determinants of crime in the main spheres of public life (economic, political, legal, socio-cultural) are investigated.